Corporate Entrepreneurship Performance : Findings From Government-Linked Companies in Malaysia - Harry, Anak Entebang; Harrison, Richard T. (Macrothink Institute, Inc., 2019)
A nation’s economic growth has been associated with the role of entrepreneurship. While recognising the work of entrepreneurship on the mindset and behaviour of individual entrepreneurs, research into an organisational perspective of entrepreneurship continues to emerge due to unprecedented developments occurring around the world over the last two decades. Notably, past studies have postulated that entrepreneurial organisations tend to perform better than conservative organisations. In this vein, the Malaysian government has set up Government-linked companies (GLCs) to enable these entities to become more effective, efficient, and competitive, which can assist the government in strengthening its economy. On the other hand, despite considerable improvements, the overall performance of GLCs has been unsatisfactory. Given the hostility and dynamism of the business environment, GLCs have no other option but to improve and perform better. Recognising this, the purpose of the study is to determine the underlying forces forcing GLCs to improve and to identify forms of corporate entrepreneurship (CE) pursued by GLCs. Building on the outcomes of semi-structured interviews with senior managers in GLCs, the need for CE is fostered by competition and market pressure, technological changes, and increases in operation costs. Finally, future studies of CE in Malaysia may consider other aspects of CE, including issues